Digital Twin Driven Intelligent Systems and Emerging Metaverse - Karaarslan, Enis, editor 655284; Aydin, Ömer, editor 655285; Cali, Ümit, editor 655287; Challenger, Moharram, editor 655288 (Switzerland: Springer, 2023)
Includes bibliographical and references